Kinetics and thermodynamics of carbon steel corrosion in different types of soil solution - Mohamad Sa’Adan, Amy Wahida (2012)
The fundamental cause of deterioration of buried pipeline is soil corrosion. Factors that influence soil corrosion includes soil type, moisture content, supply of oxygen, redox potential, pH value, soil resistivity, and microbial activity. This study investigated the effect of soil types on the corrosion of carbon steel. Three types of soil namely, laterite, yellow soil, and kaolin were taken as soil of interest. The corrosion rates of carbon steel in various types of soil solutions were studied by applying weight loss method in the temperature range of 30oC – 90oC for 1-5 days and electrochemical method based on Tafel polarization measurements. The results obtained from weight loss method and Tafel polarization measurement revealed that yellow soil has the highest corrosion rate. High corrosion rate is due to the low pH and high conductivity of yellow soil solution. The corrosion rates also increased with increasing temperature and decreased with increasing immersion time. Kinetic functions in terms of activation energy, Ea indicates that yellow soil solution has the lowest activation energy followed by laterite and kaolin which is 3.33 kJ mol-1, 5.48 kJ mol-1, and 8.82 kJ mol-1 respectively. The positive value of heat of reaction, ?H indicates that the process of interaction of chemical species in the solution of soil samples on the steel surface is endothermic. The negative value of entropy of reaction, ?S implies that the system is less disorder and decrease in randomized motion. The positive values of Gibbs free energy, ?G suggested that the corrosion reactions by chemical species in the soil solutions did not occur spontaneously. This investigation showed that the corrosion of laterite soil solution on carbon steel surface can be described as pitting corrosion which follows the Frumkin adsorption isotherm